Sustainable Education Quality Management: The Role Of Supervision In Realizing Quality Schools - Wijayanti, Ratih Kumala; Murdiani, Janti; Sutopo, Anam; Anif, Sofyan (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to analyze the role of supervision in sustainable education quality management in primary schools. The background of the study is based on the importance of supervision as a strategic instrument to improve the overall quality of education, not only as an administrative control tool. This study used a qualitative approach with data collection techniques through interviews, observation and documentation, and data analysis of the Miles and Huberman model. The results show that supervision has five main roles in improving the quality of education, namely coaching teachers, improving professional competence, monitoring and evaluating learning quality, encouraging learning innovation, and building a culture of reflection. These five roles significantly contribute to improving the quality of the learning process, teacher professionalism and the creation of a sustainable culture of quality in primary schools.